Verbal and Nonverbal Communication of Presidential and Vice-Presidential Candidates During the Third and Fourth Debates of the 2024 Election: A Semiotic Analysis by Charles Sanders Peirce - Alfiah Alfiah; Iman Mukhroman; Idi Dimyati (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
As presidential and vice-presidential candidates seek to capture public attention and understanding, they often employ innovative and creative methods. Both verbal and nonverbal messaging play a crucial role in this process. Therefore, understanding the verbal and nonverbal communication of a potential national leader is essential to prevent future misunderstandings. This study aims to analyze the political verbal and nonverbal communication of presidential (capres) and vice-presidential (cawapres) candidates during the third and fourth debates of the 2024 election using Charles Sanders Peirce's semiotic analysis. The primary focus of this research is to understand how the concepts of Sign, Object, and Interpretant are used by the candidates to convey their political messages during the debates. The methodology employed is qualitative, utilizing a semiotic analysis approach, which allows the researcher to elucidate the meanings behind the signs and symbols used in political communication. The study finds that the use of certain symbols significantly influences voter perceptions of the candidates. Additionally, the research highlights that signs play a critical role in the effectiveness of political communication, where gestures, facial expressions, and body language enhance the candidates' appeal and credibility in the eyes of the voters. These findings are expected to contribute to the development of more effective political communication strategies in future election campaigns.